Tingkat Kemampuan Penalaran Matematis Siswa Kelas IV Ditinjau Dari Gender Di SD N Galiran - Dheta Meliana Rachma; Sekar Dwi Ardianti; Eka Zuliana (PGSD Universitas Muria Kudus, 2022)
This research aims to analyze of mathematical reasoning ability student grade IV from gender in SD N Galiran.This research is quantitative correlation with correlation method. The population this research is student of grade IV in SD N Galiran in study year of 2022/2023 and than 28 student and sample with totally sampling technique. The instrument in the research is test questions of mathematical reasoning ability with 8 questions. The result in research get conclusion mathematical reasoning ability of male student is subordinate from female student with score presentation male student is 42,79% and female student is 57,20% and this research get conclusion to occur connection of mathematical reasoning ability with student gender with grade 0,142.